Survival, activity patterns, movements, home ranges and resource selection of female mule deer and white-tailed deer in western Kansas - Karish, Talesha (Kansas State University, 2022)
White-tailed deer (Odocoileus virginianus) and mule deer (O. hemionus) occur in sympatric populations across the Great Plains in North America. Mule deer abundance and occupied range has been declining during the past three decades while white-tailed deer abundance and occupied range has been increasing. Factors contributing to the dichotomous population growth and distribution patterns across their sympatric range are unknown, but potentially include differential survival, space use, and resource selection, all of which may be contributing to indirect competition that may be negatively affecting mule deer populations. Overlap in resource use or space use between mule deer and white-tailed deer could be evidence of competition or competitive exclusion. Activity patterns could provide insights for temporal segregation or competition. Differential space use could allow these species to spatially segregate and co-occur without competing for the same resources. My objectives were to 1) estimate annual and seasonal survival rates, 2) identify cause-specific mortality of adult female mule deer and white-tailed deer, 3) compare behavior patterns between adult mule deer and white-tailed deer of both sexes at seasonal and fine temporal period scales, 4) evaluate the difference in movements between adult female mule deer and white-tailed deer at seasonal and fine temporal scales, 5) test for differences in home range area and composition of adult female mule deer and white-tailed deer at seasonal and fine temporal scales, and 6) evaluate differences in seasonal multi-scale resource selection by female mule deer and white-tailed deer in western Kansas. I deployed collars on 184 pregnant females (94 mule deer and 90 white-tailed deer) at two different study sites in western Kansas (North, South) over three years, 2018, 2019 and 2020. Each deer received a high-resolution GPS/VHF collar that recorded hourly locations, activity accelerometer data along 3 axes, and used an activity sensor to identify mortality events. I used a Kaplan-Meier model to estimate cumulative weekly and annual survival and fit a hazard function to each survival model. I tested for relative influence of factors on estimated survival. I categorized activity points into three behavioral states (feeding, resting, and running). I converted activity points into a proportion of total behavior for each deer and tested for differences in the proportion of behavior categories between species and among seasons. I calculated individual hourly and daily movements seasonally and compared them between species and among seasons. I calculated annual and seasonal 95% home ranges and 50% core areas for each individual deer using a Biased Brownian Bridge movement model. Using logistic regression, I modeled resource selection by mule deer and white-tailed deer at the landscape scale, within home range scale, and within the core home range to identify selection for potential habitat variables and cover types. There was no difference in annual survival of adult female deer between species (mule deer [0.78 ± 0.04] and white-tailed deer [0.77 ± 0.05]). Harvest was the leading known cause of female mortality at 14% of the total mortality, but it was low compared to other studies in the Great Plains. Behavior of both species was similar in all seasons except for rut for males. In rut, males doubled their running behavior. Firearm season produced no changes in behavior for either species or sex. However, the greatest movements and home ranges were in the firearm season. There were greater movements and home ranges in the cold seasons than in the warm seasons. Mule deer were found to use steeper slopes than white-tailed deer, and white-tailed deer used riparian and woodland areas more than mule deer. Habitat patches enrolled in the U.S. Department of Agriculture Conservation Reserve Program were strongly selected by both species in every season and scale. Managers should focus on preserving CRP to stabilize the mule deer population. Given harvest rates of females are low, survival of adult females of both species of deer appears to be little affected by harvest, so there is no need to alter harvest rates of either species.
Keywords: Mule deer; Activity patterns; Home ranges; Resource selection; Survival; White-tailed deer